Production of bacterial lipids from hydrocarbon-based wastewaters in sequencing batch airlift reactors (SBAR) - Silva, Ana Rita (2019)
Produced water (PW) and spent oil-based wastewaters (SOW) are some of the largest oily wastewaters produced. Due to the high toxicity of hydrocarbons, these oily wastewaters need to be treated before discharge. In this work, production of bacterial lipids from SOW and PW is demonstrated in two SBAR inoculated with Rhodococcus opacus B4 and Alcanivorax borkumensis SK2, respectively. Different process conditions (carbon/nitrogen ratio and feast stage times) were tested in order to maximize neutral lipids production and hydrocarbons biodegradation. Storage lipids compounds produced by R. opacus B4 were associated with nitrogen-scarcity conditions (high Chemical Oxygen Demand (COD)/nitrogen (N) ratio) while for A. borkumensis SK2 it was growth-related (low COD/N ratio). The observed differences highlight the need for different operational strategies to optimize production of bacterial lipids from the two different oily wastewaters under study.